2013
DOI: 10.1590/s1984-82502013000400021
|View full text |Cite
|
Sign up to set email alerts
|

Floating tablets of hydralazine hydrochloride: optimization and evaluation

Abstract: Hydralazine hydrochloride has a half-life of 2 to 4 hours with an oral bioavailability of 26-50%. Since hydralazine has a demethylating effect on various suppressor genes, it can be used in various types of cancer to support chemotherapy. The purpose of this study was to optimize and evaluate floating tablets of hydralazine hydrochloride designed to prolong the gastric residence time and to provide controlled release of the drug for 14 h. The floating tablets of hydralazine hydrochloride were prepared by the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…3 ) whereas floating lag time decreases with increasing amount of sodium bicarbonate [37]. The carbon dioxide generated is widely relative to the quantity of sodium bicarbonate (NaHCO3) in the tablet.…”
Section: Floating Behavior Of Tabletsmentioning
confidence: 99%
“…3 ) whereas floating lag time decreases with increasing amount of sodium bicarbonate [37]. The carbon dioxide generated is widely relative to the quantity of sodium bicarbonate (NaHCO3) in the tablet.…”
Section: Floating Behavior Of Tabletsmentioning
confidence: 99%
“…Results of DSC studies are shown in Figures 1 and 2 . The DSC thermogram of HHC showed a broad endothermic melting peak at about 277.6°C; 29 31 this peak was retained in the same position with less intensity in physical mixture sample with d -Mannitol ( Figure 1B ), Pharmaburst ( Figure 2A ), and Saccharin ( Figure 2C ) due to drug dilution within the mixture. In case of drug physical mixture with SSG ( Figure 1C ), the drug melting peak was also retained with appearance of other sharp melting exothermic peak at 234°C.…”
Section: Resultsmentioning
confidence: 99%
“…Mughal et al [ 9 ] used the technique of extrusion and spheronization to produce hydralazine pellets. Vanitha et al [ 10 ] and Acharya et al [ 11 ] in their work dealt with the optimization and evaluation of floating tablets of hydralazine hydrochloride from granules created using wet granulation, designed to prolong the gastric residence time and to provide controlled release of the drug. Tablets must have a suitable mechanical strength to prevent chipping or breaking at manipulation, while ensuring adequate disintegration.…”
Section: Introductionmentioning
confidence: 99%